A reinvented education in Business and accounting using a GBL approach for soft skills - Bastos, Susana (2021)
The vulnerable, dynamic and digitalizing working environments of the 2020s obviously propose new types of ‘newcomer’ skills. The character of these ‘soft skills’ is inherent, whereby their learning forms a challenge for educators. Researchers around the world are on the same question: how to make the learning tools and rebuilt the classroom (virtual and face-to-face) in order to cope with this digital generation? This change needs to incorporate new Skills; these skills, called Core Skills, are changing the way to teach and to learn. Motivation is the essential key to have in mind. Creating mind-sets under a strong cognitive engagement is education for the future of professionals. Gamification, Game-Based Learning (GBL), Simulations, Virtual classrooms, digital platforms with contents and many other methods are in use all around the world to change, with motivation, the perspective of students towards their own learning path. The VUCA (volatility, uncertainty, complexity and ambiguity) world brought Higher Education Institutions the discussion of the future for an education of excellence. This article intends to present a case study as a solution to combine Simulation and GBL to promote the Core Skills that students and teachers need to achieve success on the process of teaching and learning. The solution is innovative due to the main scope: the perfect connection of humanity and empathy through the use of Simulation-GBL in higher educational institutions.